Activation and Evasion of RLR Signaling by DNA Virus Infection - Jia, Junli; Fu, Jiangan; Tang, Huamin (Frontiers in Microbiology, 2021)
Antiviral innate immune response triggered by nucleic acid recognition plays an extremely important role in controlling viral infections. The initiation of antiviral immune response against RNA viruses through ligand recognition of retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) was extensively studied. RLR’s role in DNA virus infection, which is less known, is increasing attention. Here, we review the research progress of the ligand recognition of RLRs during the DNA virus infection process and the viral evasion mechanism from host immune responses.